Perspective of perovskite-based X-ray hybrid pixel array detectors - Fiederle, Michael; Baumbach, Tilo (Frontiers in Physics, 2024)
Compound semiconductors are playing a major role in the production of X-ray pixel detectors for the application in laboratories and beamlines at photon sources. The performance of these detectors has constantly been improved for the last decades but experiments are still limited by the properties of the detector material, especially under high flux illumination. The fast development of perovskite crystals opens the possibility for new materials to be used as highly efficient X-ray pixel detectors. The published data until now, of the transport properties, demonstrate the large potential of perovskite semiconductors. The achieved values are comparable with the ones of CdTe-based detectors. This paper presents potential perovskite-based detector materials and compares their performance with the state-of-the-art CdTe-based detectors. The perspectives of perovskite semiconductors are promising for the production of large area X-ray detectors but still some challenges remain.